Hydrophilic modifications of PVDF membranes via swift heavy ion irradiations. (1st February 2018) - Sehgal, T.; Semwal, A.; Maity, G.; Patel, Shiv P.
ABSTRACT: The paper presents the hydrophilic modification of polyvinylidene fluoride (PVDF) membranes under swift heavy ion (SHI) irradiation. The research work included the irradiation of PVDF membranes of 9 μm thicknesses with 50 MeV Ni ions at fluences of 1 × 10 13 and 5 × 10 13 ion cm −2 . The pristine and irradiated membranes have been investigated by means of Fourier transform infrared spectroscopy, atomic force microscopy, scanning electron microscope and water contact angle measurement. It is observed that porosity, grain size and surface roughness of the membranes increase after ion irradiation and the water contact angle on irradiated sample decreases as compared to the pristine sample, indicating the development of a highly hydrophilic surface. The energy transferred by energetic ions to the PVDF membranes initiated the crosslinking and chain scission. The crosslinking and chain scission increase the roughness of PVDF surface which develops highly hydrophilic PVDF membranes after SHI irradiation.